MIDWIFERY CARE OF POSTPARTUM BREAST ENGORGEMENT DAY THREE USING VARNEY APPROACH: A CASE STUDY - Manurung, Revalina; Sari, Febriana; Sirait, Christina; Irmawati; Umairoh, Fifin (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Breast engorgement is one of the most common breastfeeding problems experienced during the early postpartum period, particularly between the third and fifth days after childbirth. If not managed appropriately, breast engorgement may interfere with breastfeeding, cause maternal discomfort, and increase the risk of mastitis. Midwives play a crucial role in providing evidence-based care to support successful breastfeeding. Objectives: This study aimed to describe the implementation of midwifery care for a mother with breast engorgement on the third day postpartum using Helen Varney’s seven-step approach. Methods: A descriptive case study design was employed. Data were collected through interviews, observation, physical examination, and documentation. Midwifery management was conducted according to Helen Varney’s seven-step approach, including assessment, diagnosis, identification of potential problems, immediate intervention, planning, implementation, and evaluation. Results: Mrs. R, a 28-year-old multiparous mother, experienced breast engorgement on the third postpartum day, characterized by breast swelling, pain, firmness, and difficulty breastfeeding. Interventions included breastfeeding education, correction of infant positioning and latch, breast care, cold compress application, and family support. Evaluation showed a reduction in pain intensity, decreased breast swelling, improved milk flow, and more effective breastfeeding. Conclusions: The application of Helen Varney’s seven-step approach effectively reduced symptoms of breast engorgement and improved breastfeeding outcomes. Early identification and appropriate midwifery interventions are essential to prevent complications and promote exclusive breastfeeding.